Preparation and Characterization of Pullulan/Poly(N-vinylimidazole) Gels - Hezarkhani, Marjan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Pullulan/Poly(N-vinylimidazole) (PNVI) hybrid materials have been prepared and characterized according to their physicochemical properties. Graft copolymerization and cryopolymerization/cryogelation approaches were applied in the preparation of pullulan/poly(N-vinylimidazole) samples. Graft copolymerization of PNVI onto pullulan backbone was studied in aqueous solution by using ammonium persulphate initiation. A maximum grafting yield of 513% was obtained using 8.00 g/L pullulan, 0.66 M NVI and 0.18 M ammonium persulphate at 40°C for 3 h reaction duration conditions. Water soluble pullulan-graftPNVI samples were obtained that exhibited antibacterial and antifungal activities. These samples precipitate out of solution via complex formation with polyanions such as tripolyphosphate and citrate ions. Epichlorohydrin (ECH) crosslinked pullulan gel was used as substrate for grafting of PNVI to obtain pullulan/PNVI hybrid gels. The maximum grafting yield obtained for pullulan-ECH-graft-PNVI samples was 189% when 8.0 g/L pullulan gel, 0.57 M NVI and 0.18 M ammonium persulphate were used at 40°C for 3 h reaction duration conditions. Lower grafting yields were obtained due to the heterogeneous nature of the reaction medium when compared to the grafting yields in solution. Pullulan-ECHgraft-PNVI exhibit superabsorbency within 700-1300% and 6000-8500% ranges equilibrium water retention capacity in distilled water and in aqueous acidic medium respectively. Cryogels of pullulan in the presence of ECH, PNVI cryogels in the presence and in the absence of ECH and pullulan/PNVI cryogels in the presence of ECH were prepared. Product yields and gel fraction yields were determined and correlated with cryogel preparation conditions. Similar to pullulan-ECH-graft-PNVI samples, the cryogels acted as hydrogels with maximum equilibrium swelling capacities of 425%, 240%, 270% and 620%, for pullulan-ECH, PNVI, PNVI-ECH, and pullulan-ECH-PNVI cryogel samples, respectively

ÖZ: Bu tez çalışmasının konusu pululan/poly(N-vinylimidazole) hibrit malzemelerin hazırlanması ve fizikokimyasal özelliklerinin belirlenmesidir. Bu malzemelerin hazırlanmasında aşı kopolimerizasyonu ve kriyopolimerleşme ve kriyojelleşme yöntemleri kullanılmıştır. Homojen ortamda, sulu çözeltide amonyum persülfat başlatıcı varlığında hazırlanan aşı kopolimerlerin için en yüksek aşılanma yüzdesi 8.00 g/L pullulan, 0.66 M NVI ve 0.18 M ammonium persulphate, 40°C, 3 saat koşullarında, 513% olarak bulunmuştur. Bu örneklerin suda çözündükleri, antibakteriyal ve antifungal aktiviteye sahip oldukları ve polianyonlarla kompleks yaparak çökeldikleri gözlemlenmiştir. Epichlorohydrin ile çapraz bağlanmaya uğratılarak elde edilmiş olan pululan-ECH jeller ise heterojen ortamda poly(N-vinylimidazole) ile aşılanmış ve en yüksek 189%, 8.0 g/L pullulan jel, 0.57 M NVI ve 0.18 M ammonium persulphate, 40°C, 3 saat, aşılanma yüzdesine ulaşılmıştır. Ortamın heterojen olması nedeniyle aşılanma yüzdeleri çözelti içinde elde edilen kopolimerlere göre daha düşüktür. Bu örnekler sulu ortamda süperabsorban hidrojel davranışı göstererek saf su içinde %700-%1300 ve asitli, sulu ortamda %6000-%8500 aralığında su tutma kapasitesine sahip olduklarını göstermişlerdir. Pululan-ECH, PNVI, PNVI-ECH ve pululan-ECH-PNVI kriyojeller elde edilmiş ve ürün yüzdeleri ile jel fraksiyonları kriyojel hazırlama koşullarına göre analiz edilmiştir. Bu jellerin de hidrojel davranışı gösterdikleri ve sırasıyla pululan-ECH, PNVI, PNVI-ECH ve pululan-ECH-PNVI kriyojellerin en yüksek su tutma kapasitelerinin dengede 425%, 240%, 270% ve 620% olduğu gözlemlenmiştir. Örnekler, elemental analiz, FTIR-ATR, H-1 NMR, TGA, XRD ve SEM analiz yöntemleri ile karaktarize edlmişlerdir. Fizikokimyasal özellikler, örneklerin hazırlnama koşulları ve yapılarına göre değerlendirilmiştir
Doctor of Philosophy in Chemistry. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2019. Supervisor: Supervisor: Prof. Dr. Elvan Yılmaz.
Keywords: Thesis Tez; Chemistry Department; Pullulan; poly(N-vinylimidazole); graft copolymer; cryogel; hydrogel